Impact of solar-driven heating strategies on the phase change thermal storage performance of erythritol - Deng, Yuxuan; Zhen, Yu; Zhu, Xiaojuan; Li, Yanna; Xu, Jing (Frontiers in Chemistry, 2024)
With escalating energy demands, solar power stands out for its abundance and renewable advantages, presenting a paramount sustainable solution. Herein, we tactically incorporate phase change material (PCM) into solar energy systems, resulting in substantial enhancements in energy storage and utilization. Through numerical simulations, the thermal dynamics and phase change processes associated with various heating methodologies are investigated, aiming to achieve optimal thermal performance and energy efficiency. Detailed analysis of temperature dynamics within the PCM under two distinct heating methods reveals pivotal thermal fluctuations in both the PCM and water during heat release. The results indicate that bottom heating promptly induces rayleigh convection, resulting in a uniform temperature and a stable phase interface, which are desirable for heat transfer. In contrast, central tube heating concentrates heat transfer in the upper PCM layer, leading to an uneven phase interface and thermal stratification. Configurations with two horizontally aligned heating tubes result in a 36% reduction in melting duration compared to the single central tube setup, highlighting enhanced efficiency. Additionally, the bottom heating approach demonstrates improved energy storage efficiency in both the initial and second heating cycles. These findings highlight the potential of PCM-integrated combined heating systems for solar energy capture, confirming their efficiency and practicality in addressing modern household energy demands.